Bahasa Inggris Bahasa Inggris: Bahasa Inggris - Muchlis, Zaini; Atsauri, Imam Sufyan; Sukron, Ahmad (Peradaban Journal of Religion and Society, 2024)
Leaders possess multifaceted understanding to resolve the various problems within the government. In Indonesia, leaders can instill Islamic and Indonesian values to foster patriotism and respect for diversity, which are central to Islamic teachings. The influence of globalization has led to Indonesian leaders’ difficulty to integrate Islamic and Indonesian values. The lack of comprehension among leaders regarding these values is a primary factor in the divergence of Islamic and Indonesian principles. This paper educates future leaders and provides them with leadership concepts. This study employs a literature review by collecting various books as references. Nurcholish Madjid’s trilogy of thought provides a complex foundation for leadership to reconcile Islamic and Indonesian principles. Islam as Rahmatan lil ‘Alamin, Modernization and Postmodernity in Islam, and Islamic Indonesianness are Nurcholish Madjid’s ideas that can be implemented in leadership approaches such as Inclusivity in Leadership, Adaptation to Change, and Strengthening Pancasila Values. Madjid’s trilogy is a valuable resource for leadership in Indonesia, particularly in building unity while respecting identity or background. Islamic values with nationalistic principles can ultimately be understood as a form of harmonious integration capable of adapting to global developments.